Awareness assessment for viral hepatitis among patients in different departments of medical institutions and students. - Loboda, A. M.; Malysh, N. G.; Melekhovets, O. K.; Chemych, O. M.; Mogylenko, V. I.; Osypko, D. V. (Journal of Education, Health and Sport, 2021)
The significant spread of chronic viral hepatitis in Ukraine and the whole world, an increase in the incidence of medical personnel, and the lack of wariness of the population regarding the diseases of this group make it necessary to have a statistical analysis of the etiology, diagnosis, treatment, and prevention of viral hepatitis among different population groups. Aim. To study and analyze the awareness about viral hepatitis B (HBV) and C (HCV) of patients who undergo treatment in various departments (infectious, surgical, therapeutic) and the students who didn't take the course of infectious diseases. Materials and methods. A questionnaire was developed to establish the level of awareness among patients with viral hepatitis. The study was conducted through a sociological survey (full-time, one-time, individual) with the preservation of confidentiality conditions. The study was conducted in the infectious department of Sumy Regional Infectious Diseases Clinical Hospital named after ZY Krasovitsky, Surgical Department of Sumy City Clinical Hospital №5, therapeutic department of Sumy Regional Clinical Hospital of the 4th year of Sumy State University Medical Institute in 2019. In total, 147 people took part in the survey: 20 were in treatment at the therapeutic ward, 20 - in the surgical ward, 20 - in the infectious diseases department, and 20 - 4th-year students. Conclusions. Viral hepatitis is currently one of the most pressing health problems. It is used for the sociological survey we developed to determine the level of knowledge of the population about the causative agent of viral hepatitis, transmission, prevention (not specific and specific), clinical features, laboratory methods of diagnosis, and treatment. Among all the surveyed results, recipients gave most of the correct answers to questions about the causative agent of viral hepatitis and transmission routes. The worst known are patients in the surgical wards about the presence of an effective hepatitis B vaccine (20.00%); patients of infectious and therapeutic wards (20.00% each) and 4th-year students (25.00%) - about the presence of effective hepatitis C therapy; (95.00%) and a reference group of physicians (100.00%) on the etiology of viral hepatitis. Patients in surgical wards (84.30%) answered the most frequently asked questions about the ways of transmission of viral hepatitis.